1998
DOI: 10.1128/jcm.36.7.1989-1995.1998
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step Multiplex PCR Assay for Characterization of New World Leishmania Complexes

Abstract: We have developed a PCR assay for one-step differentiation of the three complexes of New World Leishmania (Leishmania braziliensis, Leishmania mexicana, andLeishmania donovani). This multiplex assay is targeted to the spliced leader RNA (mini-exon) gene repeats of these organisms and can detect all three complexes simultaneously, generating differently sized products for each complex. The assay is specific to theLeishmania genus and does not recognize related kinetoplastid protozoa, such as Trypanosoma cruzi,T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
15

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 51 publications
1
62
1
15
Order By: Relevance
“…PCR has the added advantage of identifying the subtypes of leishmania parasites. [7][8][9]22,23 In recent studies, Brujin MHL et al . reported that positive detection rates were 38.5% by direct visualization of smear and 84.6% by PCR.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…PCR has the added advantage of identifying the subtypes of leishmania parasites. [7][8][9]22,23 In recent studies, Brujin MHL et al . reported that positive detection rates were 38.5% by direct visualization of smear and 84.6% by PCR.…”
Section: Figurementioning
confidence: 99%
“…Sometimes biopsy material had been badly handled or fixed, making interpretation of the pathology and identification of the parasites impossible; however, even in such tissues, detection of parasite DNA is possible by PCR. [7][8][9]22,23,24 Although direct microscopy is a simple and a rapid technique, it may not detect parasites. Culture may be contaminated and thus take a long time to obtain a result.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The collaboration with the Department of Parasitology began in 1988, first with support of biochemical and immunological diagnostic and typing methods and then with the introduction of simplified PCR techniques for the diagnosis and characterization of leishmaniasis, which have been used routinely for the last 17 years. 12 New molecular typing methods were also developed, 13 and use of these assays in-country led to the discovery of a new form of disease caused by Leishmania chagasi infection in Nicaragua (atypical cutaneous leishmaniasis [ACL]). 14 Further studies examining the parasitological, immunological, epidemiological, and entomological characteristics of ACL were conducted, and the Ministry of Health incorporated information about recognition, diagnosis, and treatment of ACL into posters that were distributed throughout the nation's health centers.…”
Section: A Long-term Approach: the Nicaraguan Success Storymentioning
confidence: 99%
“…It is a widely utilized assay for specifically amplifying small fragments of nucleic acid. In the field of infectious diseases, multiplex PCR has been proven to be a valuable tool for identification of viruses (Stockton et al 1998), bacteria (Kong et al 2002) and parasites (Harris et al 1998).…”
Section: Introductionmentioning
confidence: 99%